Tuturan Ajakan Bahasa Jepang dengan Menggunakan Strategi Kinesik - Rani Wulansari Ariana (Jurnal Sastra - Studi Ilmiah Sastra, 2022)
The data of this study were dialogic discourse which analyzed using descriptive methods. The data were collected using observation and writing technique. The data of nonverbal communication documented through photos using a recording technique. Nonverbal strategies used by speaker to force hearer to follow a speaker invitation are: haptic by touching or grasping hearer’s hand, gestures by appointing an item or places (kinesics or body movement), and eye contact or oculesics by maintaining eye contact with the hearer. The results are when the situation was calm speaker uses touch or haptic by touching the hands of the hearer but when the situation was urgent, the speaker uses haptic by holding hands and running or walking together.